(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The aim of this research is to highlight the importance of reducing the cost of a flight ticket by using information technology and the Internet, in the process of purchasing tickets for electronic flights, and to shift from the traditional method of purchasing and payment operations to the electronic method, to reduce the financial and non-financial risks associated with the traditional purchase process, as well as saving the cost Time, effort and money for the customer, and the researcher used the deductive approach in linking the variables (Internet of Things technology and reducing the costs of air tickets) with the aim of evaluating the cost system in force in (the General Company of Iraqi Airways) from the perspective of adding new services at low costs and excluding high-cost services loaded on the ticket, the researcher also used the inductive method and carried out a survey of studies that presented the research variables in order to extract ideas and compile the theoretical foundations presented in books, periodicals, conferences, and related researches, whether Iraqi, Arab, or foreign. used in the Iraqi Airways General Company, in addition to field visits and personal interviews with the relevant parties in the research sample company outside it.This research also shows part of the knowledge foundations for cost reduction and the technology of the Internet of Things, as well as an indication of the amount of reduction in the cost of the electronic ticket for the flights of the General Company of Iraqi Airways, when purchasing via the Internet instead of going to the offices selling traditional (paper) tickets. The research reached the most important results: -There is a clear difference of (25) dollars between the commission of the electronic system for purchasing electronic tickets through the proposed application (program), which amounts to (1) dollars, and the commission of agents selling traditional paper tickets, which amounts to (26) dollars, which is avoided being charged on tickets for different flights as a result of using The technology of the Internet of Things in the process of selling electronic tickets, this difference led to a contribution to reducing the cost of tickets for the research sample and thus lowering their price.Several recommendations were made in the research, the most important of which are: -The company must develop the Internet of Things technology for selling tickets via the Internet and design an application (program) for buying flight tickets for smart devices belonging to the company that provides new services for travelers, which reduces the cost of traditional activities and improves ticket sales for travelers.